2010
DOI: 10.1016/j.clim.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A protective role of Mer receptor tyrosine kinase in nephrotoxic serum-induced nephritis

Abstract: The Mer receptor tyrosine kinase is strongly expressed in the glomerulus. We wondered if this molecule might modify immune-mediated glomerular disease through its functions as a receptor for apoptotic cells and immunoregulatory molecule. Mer-knockout (KO) mice showed decreased survival rate and greatly increased proteinuria and serum urea levels compared to wild type (WT) mice by day 3 after injection of NTS. Their glomeruli were hyperplastic and later became necrotic. While in the glomerulus of WT mice, a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 35 publications
(44 reference statements)
9
41
0
Order By: Relevance
“…The C T of each test message was first normalized using the C T for GAPDH, assayed in the same sample. Fold change was then calculated (19). …”
Section: Methodsmentioning
confidence: 99%
“…The C T of each test message was first normalized using the C T for GAPDH, assayed in the same sample. Fold change was then calculated (19). …”
Section: Methodsmentioning
confidence: 99%
“…Our previous work showed that there is accelerated and more severe NTS-nephritis in the absence of Mer (5). We now show that Axl-KO mice, in contrast, develop reduced renal inflammation with significantly improved survival rate and reduced blood urea nitrogen (BUN), as compared to NTS-treated WT, Mer-KO, and Axl/Mer-double knockout (A/M-KO) mice.…”
Section: Introductionmentioning
confidence: 96%
“…Mice lacking Mer single or TAM triple receptors developed mild or severe lupus-like autoimmune disorders, respectively (14, 15). Mer is highly expressed in glomeruli and functions in the suppression of inflammatory responses and in the clearance of apoptotic cells (5, 14). Mer-KO mice respond to inflammatory stimuli by producing increased proinflammatory mediators such as IL-1, IL-6, and TNFα (5, 20, 21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of Mer, in contrast to Axl, inhibits glomerular inflammation during glomerulonephritis. 65 In antigen-presenting cells, TAM receptor signaling inhibits lipopolysaccharide (LPS)-induced cytokine production (eg, tumor necrosis factor-a [TNF-a]).…”
Section: Tam Receptorsmentioning
confidence: 99%